The Representation of Feminist Ideologies in Roald Dahl’s Matilda - Suwastini, Ni Komang Arie; Utami, Ida Ayu Made Istri; Pramestika, Ni Luhde Meidy; Wahyuni, Luh Gede Eka; Rusnalasari, Zulidyana Dwi (Universitas Pendidikan Ganesha, 2021)
Matilda is one of Roald Dahl's greatest works. In this novel, the titular character, Matilda, is described as a five-year-old girl Matilda with extraordinary ability, despite her unfavorable family. She was fortunate to meet a dedicated teacher, Miss Honey, who recognized her talents. The present study aimed at analyzing Roald Dahl’s novel entitled Matilda from feminist perspectives. This study focused on analyzing feminism represented in the novel’s intrinsic elements. The study employed close reading enriched with Rosemary Tong's elaboration on feminist perspectives. The analysis revealed that feminist ideologies are represented through the novel’s theme, setting, and characterizations of the major characters. The novel's theme represents feminist ideologies by presenting women against, abused, or embraced feminist ideologies. The socio-cultural setting of the novel further emphasized the oppression of women who wanted to be independent. The depiction of feminism was strongly presented in the characterizations of Matilda and Miss Honey, who cooperated in fighting against their families' patriarchal treatment. These results imply that the novel is educative for children and young women to raise awareness about gender equality.